2012
DOI: 10.3390/molecules17043917
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Antimicrobial Properties and Phenolics of Different Solvent Extracts from Bark, Leaves and Seeds of Pongamia pinnata (L.) Pierre

Abstract: This study appraises the antioxidant and antimicrobial attributes of various solvent extracts (absolute methanol, aqueous methanol, absolute ethanol, aqueous ethanol, absolute acetone, aqueous acetone, and deionized water) from bark, leaves and seeds of Pongamia pinnata (L.) Pierre. Maximum extraction yield of antioxidant components from bark (16.31%), leaves (11.42%) and seeds (21.51%) of P. pinnata was obtained using aqueous methanol (20:80). Of the extracts tested, the bark extract, obtained with aqueous me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 30 publications
5
33
1
4
Order By: Relevance
“…In very recent studies, Sharma et al (2012) used chloroform, methanol and water extracts of P. pinnata against three species of Trichophyton and two species of Microsporum where chloroform extracts (1.25-10.00 MIC) were more effective than the methanol extracts. Methanol, ethanol, acetone (both absolute and aqueous) and de-ionized water extracts of bark, leaf and seeds of the pant were evaluated where the bark extracts against a set of bacterial and fungal strains revealed strongest antimicrobial activity with the largest ZI and lowest MIC values (Sajid et al 2012). These findings corroborate to those reported here using D. indica extractives.…”
Section: Indica Extracs In Chloroformsupporting
confidence: 81%
See 2 more Smart Citations
“…In very recent studies, Sharma et al (2012) used chloroform, methanol and water extracts of P. pinnata against three species of Trichophyton and two species of Microsporum where chloroform extracts (1.25-10.00 MIC) were more effective than the methanol extracts. Methanol, ethanol, acetone (both absolute and aqueous) and de-ionized water extracts of bark, leaf and seeds of the pant were evaluated where the bark extracts against a set of bacterial and fungal strains revealed strongest antimicrobial activity with the largest ZI and lowest MIC values (Sajid et al 2012). These findings corroborate to those reported here using D. indica extractives.…”
Section: Indica Extracs In Chloroformsupporting
confidence: 81%
“…For example, root bark, leaves, flowers and seeds have medicinal properties and so this is traditionally used as a medicinal plant (Sangwan et al 2010). Antifungal activities of the plant have been demonstrated by a number of recent workers (Biswal et al 2011;Johnson et al 2011;Sharma et al 2011a,b) whereas antibacterial properties of D. indica were tested among others by Wagh et al (2007), Arote et al (2009), Kogithoju et al (2012 and Sajid et al (2012). In addition, antihelmintic (Biswal et al 2011), antidiabetic (Jagadeesha 2011) and anti-dermatophytic properties (Sharma et al 2012) of the plant have recently been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Petroleum ether extract contains fats and fixed oil while aqueous extract contains amino acids, tannins (condensed and pseudo tannins) and starch [5]. IR has been reported to possess various pharmacological actions, mainly antidiabetic [6], antiinflammatory [7], nephroprotective [8], antibacterial [9], antioxidant and antimicrobial activity [10]. Further, the principle constituents of IR such as sinapic and ferulic acids have exhibited behavioural and pharmacological…”
Section: Introductionmentioning
confidence: 99%
“…All parts of this plant are used in the treatment of abscess, bronchitis, diarrhea, itches, piles, skin diseases, tumors, painful rheumatic joints, ulcers, whooping cough quench dipsia in diabetes, blood purifier and as an antiseptic to treat wounds and cuts. [6,7] Some of the reported activities of this plant include antioxidant, [8][9][10] antimicrobial, [11,12] anti-inflammatory, [13] antiulcer, [14] antihyperglycemic [15] amongst others.…”
Section: Introductionmentioning
confidence: 99%